Evaluation of the Quality of Online Information on Sudden Sensorineural Hearing Loss. Issue 2 (February 2022) - Simani, Liam; Oron, Yahav; Handzel, Ophir; Eta, Rani Abu; Warshavsky, Anton; Horowitz, Gilad; Muhanna, Nidal; Ungar, Omer J.
Abstract : Objective: To evaluate the quality of leading Internet resources of information on sudden sensorineural hearing loss (SSNHL). Study Design: Cross-sectional descriptive design. Settings: An online search by means of the Google search engine. Methods: An online search was conducted using terms related to SSNHL. We defined "quality" according to scaled readability measures (Flesch Reading Ease [FRE] and Flesch-Kincaid Grade-Level [FKGL]), as well as "understandability" and "actionability" (Patient Education Materials Assessment Tool), and Clinical Practice Guideline (CPG) adherence. Scoring was performed by two independent physicians. Results: The 10 most frequently encountered patient education websites were analyzed. The average FRE score was "fairly difficult" (mean 57.28, median 55.55, range 46.4–71.8) and the average FKGL score was "standard" (mean 9th grade, median 9th grade, range 5th–10th grade). Nine websites were understandable (mean 83%, median 84%, range 69–100%), and seven had good actionability scores (mean 73%, median 75%, range 50–100%). Most websites conformed with the CPG for patient education at a reasonable level (mean 5.6, median 5.5, range 3–7). Notably, all websites encouraged seeking medical help. Conclusion: Internet resources for patient education on SSNHL vary in quality and are generally understandable to the average layman. There is still much room for better, more comprehensive and easier-to-read information to improve patients' medical knowledge about their condition. Level of Evidence : 1 Abstract : Supplemental Digital Content is available in the text